2008
DOI: 10.1103/physrevlett.101.155501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copassivation of Cl and Cu on CdTe Grain Boundaries

Abstract: Using a first-principles method, we investigate the structural and electronic properties of grain boundaries (GBs) in polycrystalline CdTe and the effects of copassivation of elements with far distinct electronegativities. Of the two types of GBs studied in this Letter, we find that the Cd core is less harmful to the carrier transport, but is difficult to passivate with impurities such as Cl and Cu, whereas the Te core creates a high defect density below the conduction band minimum, but all these levels can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 19 publications
8
69
0
Order By: Relevance
“…The majority of copper is segregated at the grain boundaries, where it is involved in passivation of defects. DFT calculations show that both Cu’ Cd and Cu • i can be formed at the grain boundaries [31]. These defects have the opposite effect on mobility as they have on charge carrier concentration: at small Cu concentrations, the Cu’ Cd defect is formed, which appears to have a detrimental effect on mobility.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of copper is segregated at the grain boundaries, where it is involved in passivation of defects. DFT calculations show that both Cu’ Cd and Cu • i can be formed at the grain boundaries [31]. These defects have the opposite effect on mobility as they have on charge carrier concentration: at small Cu concentrations, the Cu’ Cd defect is formed, which appears to have a detrimental effect on mobility.…”
Section: Resultsmentioning
confidence: 99%
“…23,25,38 Previous studies based on the prototype GBs showed that only the Cl from CdCl2 post-treatment contributed to the improvement, because ClTe eliminated the deep-level states induced by the GBs in the gap. 6 However, the present study clearly shows that the prototype structure is not energetically the most favorable, so the mechanism of CdCl2 post-treatment should be revisited.…”
Section: Novel Understanding On Cdcl2 Post-treatmentmentioning
confidence: 99%
“…Cl concentrating at GBs was deservedly considered as the most important dopant to cure the GBs' defect levels. 6,21,22,23 We show that the Cl dopant in these new GB structures 21,23 induces ntype levels, contributing to the separation of electron-hole pairs, 22,24,25 while the Cd dopant, whose role was neglected in previous studies, facilitates the formation of selfpassivating GBs that enhance the photovoltaic efficiency. These results change the conventional picture about how the CdCl2 post-treatment improves the photovoltaic efficiency of polycrystalline CdTe solar cells, and also manifest that the previous studies on the most stable Σ3 GBs in a series of semiconductors should be revisited.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations